The Agrobacterium tumefaciens virulence gene chvE is part of a putative ABC-type sugar transport operon. - Kemner, J M (1997)
The Agrobacterium tumefaciens virulence determinant ChvE is a periplasmic binding protein which participates in chemotaxis and virulence gene induction in response to monosaccharides which occur in the plant wound environment. The region downstream of the A. tumefaciens chvE gene was cloned and sequenced for nucleotide and expression analysis. Three open reading frames transcribed in the same direction as chvE were revealed. The first two, together with chvE, encode putative proteins of a periplasmic binding protein-dependent sugar uptake system, or ABC-type (ATP binding cassette) transporter. The third open reading frame encodes a protein of unknown function. The deduced transporter gene products are related on the amino acid level to bacterial sugar transporters and probably function in glucose and galactose uptake. We have named these genes gguA, -B, and -C, for glucose galactose uptake. Mutations in gguA, gguB, or gguC do not affect virulence of A. tumefaciens on Kalanchoe diagremontiana; growth on 1 mM galactose, glucose, xylose, ribose, arabinose, fucose, or sucrose; or chemotaxis toward glucose, galactose, xylose, or arabinose.